Knowledge, attitude, and Practice of College of Home Economics (CHE) undergraduate students on nutrition facts panel use - Lopez, Noymee Anne E.; Luna, Myrna Benita Z. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
Barriers to Nutrition Facts Panel (NFP) use of CHE undergraduate students were identified in this study. Specifically, the level of knowledge, attitude, and practice (KAP) of the students on NFP use and the association between KAP was determined using the adapted cognitive and behavior model (Azanza & Zamora-Luna, 2005). A validated and pre-tested self-administered survey implemented online and paper-based was used for data collection. Barriers identified were NFP-specific, consumer-specific, and product specific. NFP-specific barriers were namely: complicated numerical expressions, difficult nutritional terminology, too much/ not enough information presented, small text size, difficult nutrient value calculations, not visible in the packaging, unappealing presentation, give bad food connotation, and inconsistent format. Consumer-specific barriers were lack of knowledge, lack of/ no interest, out of habit, complacency, unhealthy mindset, processed food restrictive diet, selective reading, personal preference, and product and/ or brand loyalty. Product-specific barriers were sensory quality, expiration date, and price and availability. The determined level of KAP of the students is familiarity, commitment and non-adoption, respectively. The adapted model was found inapplicable to NFP use due to its simplicity, hence, revised. In the revised model, no levels were present and new sub-categories for KAP were added. Significant associations were found between knowledge and practice, and attitude and practice. Suggested points of improvement for the existing NFP in the Philippines focused on format improvement and consumer education implementation. Hence, study implementation to other respondents and improvement of the questionnaire was recommended. Moreover, testing the recommended ways of improving the suggested label should be done to know whether they are effective in addressing the barriers to NFP use.
Thesis (B.S. Food Technology)---University of the Philippines Diliman
Keywords: University of the Philippines Diliman, College of Home Economics -- Undergraduates -- Attitudes; Food -- Labeling -- Philippines